Efficacy of various compatible insecticides for management of Sesame phyllody: Efficacy of various compatible insecticides for management of Sesame phyllody - K N GUPTA,; A K PANDAY,; RAJNI BISEN, (Journal of Oilseeds Research, 2023)
A field experiment was conducted during 2018 at research area of AICRP on Sesame and Niger for the effective management of phyllody in sesame. The experiment comprising eight treatments ( T1- Seed treatment with Imidacloprid 17.8 SL@ 5ml/kg seed; T2- T1+ Spray of Imidacloprid 17.8% SL @ 0.25ml/l; T3- T1 + Spray of Acetamaiprid @ 0.3g/l; T4- T1 + Spray of Thiocloprid @ 1ml/l; T5- T1 + Spray of Thiomethaxam @ 0.25 g/l; T6- T1+ Spray of Lambda cyhalothrin@ 1ml/l; T7- T1 + Spray of Azadirachtin @ 0.03%;T8- Control was laid out in Randomized Block Design with three replications. Among the eight treatments tested a positive and significant response was found with the seed treatment of imidacloprid 17.8 SL @ 5 ml/kg + spray of Acetamaiprid 20% SP @ 0.3 g/L recorded the least disease incidence (7.05 per cent) and maximum seed yield (5.21 q/ha). The results on benefit cost ratio revealed that highest benefit cost ratio was recorded in treatment T3 (4.39). All the treatments are superior over the control.